Estudo em microescala da conversão térmica e catalítica da borra do óleo de algodão para obtenção de bioquerosene - Souza, Tarciane Greyci dos Santos (2015)
This study aimed to apply the micropirólise and catalytic and non-catalytic microhidropirólise, in assessing the production of bio-kerosene from the cotton oil sludge. Samples of cotton oil sludge were provided by the Northeast Center for Strategic Technologies - CETENE (experimental Plant Caetés-PE) and makes up a major waste of the productive chain of biodiesel plant. The pyrolysis was performed using 50 mg of biomass. In hidropirólises and pyrolysis temperatures were used 500 ° C and 550 also being investigated the influence of dispersion of the catalyst in the sample. The catalysts PMZ, PWZ, MT and WT tested at 10% (m/m) in the study, were produced based on the application for the petrochemical industry and are as novel for this type of application. The obtained solutions were analyzed by GC-FID and GC / MS, and the gases produced were analyzed and quantified micro-GC. The use of hydrogen gas did not minimize the production of alkenes in pyrolysis. The presence of water in the biomass optimized thermal cracking process. This cracking when performed in the presence of catalysts at 550 °C showed a higher yield of liquid biofuel to hydrocarbons in the C9 to C16 range (approximately 37%) compared to the non-catalytic treatment. The semi-quantitative analysis of gases produced in the pyrolysis suggested routes decarboxylation (in the presence of CO2) and decarbonylation (the CO present) during the catalytic thermal cracking, and demonstrate the occurrence of the Fischer-Tropsch process produces hydrocarbons in the range kerosene.